(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This study has been attempted to assess the impact demonetization had on the lives and daily lifestyle of the common man in India. The study analyzes the impact through the various parameters which are an important part of the life structure of the Common Man in India. The study also facilitates to have a glimpse regarding the various demographic parameters that have been affected by the demonetization like the age group, occupation, locality, annual income. The findings of the study may be limited but it can definitely provide an overview of the impact that demonetization has had of common man in India. It also provides a narrow perspective response of the common man towards the demonetization, that is, whether they believe it to be good for them or the other way round. Descriptive Research design has been used by the researcher to express the data about the problem that is being studied. For achieving the objectives of the study data has been collected by primary as well as secondary sources.